Impact of hospital Type II violent events: Use of psychotropic drugs and mental health services. Issue 6 (13th February 2014) - Dement, John M.; Lipscomb, Hester J.; Schoenfisch, Ashley L.; Pompeii, Lisa A.
<x xml:space="preserve">Abstract</x> Background While violence can adversely affect mental health of victims, repercussions of violence against workers is not as well characterized. Materials and Methods We explored relationships between workplace violent events perpetrated by patients or visitors (Type II) against hospital employees and the employee use of psychotropic medications or mental health services using a data system that linked violent events with health claims. Results Significant associations were observed between reported Type II workplace violent events and employee prescription claims for anti‐depressants and anxiolytics combined (RR = 1.45, 95% CI = 1.01–2.33) and anti‐depressants alone (RR = 1.65, 95% CI = 1.10–2.48). No significant association between reported violent events and health claims for treatment of depression or anxiety was observed. Conclusions Type II violence experienced by hospital workers may lead to increased use of psychotropic drugs, particularly anti‐depressants but also anxiolytics. Our results suggest an important role of employee assistance programs in mitigating the psychological consequences of workplace violent events. Am. J. Ind. Med. 57:627–639, 2014. © 2014 Wiley Periodicals, Inc.